Preparation method and application of corrosion-resistant broadband carbon-based wave-absorbing material
By using high-voltage DC arc discharge method to prepare carbon nanoangle composite materials in harsh marine environments, the problem of poor stability of magnetic/carbon composite wave absorbing materials in harsh environments is solved, and the preparation of corrosion-resistant broadband carbon-based wave absorbing materials is realized, with high stability and excellent wave absorbing performance.
Patent Information
- Application Number
- CN202510041976.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing magnetic/carbon composite wave absorbing materials have poor stability in harsh marine corrosion environments with high temperature, high humidity and high salt spray, shorten their service life, affecting the radar wave absorbing effect.
The carbon nanoangle composite material was prepared under a nitrogen and argon atmosphere by using positive high-voltage DC arc discharge method. By inserting titanium wire and molybdenum wire into the anode carbon rod, nitrogen-doped carbon nanoangle composite material coated with MoC and TiC nanoparticles was synthesized in one step.
The corrosion-resistant broadband carbon-based absorbent materials are produced with high purity, low cost, low density and high stability. They can delay corrosion in harsh marine environments, meet the needs of absorbing waves, and show excellent absorbing performance and wideband.
Smart Images

Figure BDA0005237226100000071 
Figure BDA0005237226100000081 
Figure HDA0005237226110000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing absorbing materials, and in particular relates to a preparation method and application of a corrosion-resistant broadband carbon-based absorbing material. Background Art
[0002] Carbon materials have attracted much attention in the field of electromagnetic wave absorption due to their advantages such as high electrical conductivity, high specific surface area, low density and high chemical stability. However, due to the single loss mechanism of single-component carbon materials, it is often difficult to obtain good impedance matching. Therefore, magnetic metals (such as iron, cobalt and nickel) and their oxides are often introduced into carbon-based materials to improve the wave absorption performance. Magnetic / carbon composite materials can combine the dielectric properties of carbon materials and the magnetic properties of magnetic materials to show excellent wave absorption performance. In addition to excellent wave absorption performance, excellent wave absorbing materials also need to adapt to practical applications. In practical applications, ships are faced with harsh marine corrosion environments such as high temperature, high humidity and high salt spray. Traditional magnetic materials (such as iron, cobalt and nickel) have poor stability and are prone to aging and failure. The service life is greatly shortened compared to other application environments, which seriously affects the overall radar wave absorption effect of the ship. Therefore, how to improve the corrosion resistance of magnetic / carbon composite wave absorbing materials is an urgent problem that needs to be solved for magnetic / carbon composite wave absorbing materials.
[0003] Molybdenum carbide (Mo3C2, Mo2C and MoC) as a transition metal carbide has good corrosion resistance, oxidation stability and thermal stability, and also has certain magnetism, which can be used as an ideal magnetic component in magnetic / carbon composite absorbers. The current synthesis methods are mainly through direct high-temperature synthesis, chemical vapor deposition, etc. These methods need to be completed at a relatively high temperature, and the product purity may be poor due to uneven reaction. In addition, the electromagnetic wave loss capacity of a single molybdenum carbide material is poor, and the absorption bandwidth needs to be further improved. However, molybdenum carbide has a high density and heavy weight, which is not conducive to the formation of lightweight absorbers.
[0004] Carbon nanohorn materials prepared by arc discharge method are a new type of carbon material. In addition to the characteristics of carbon materials, they also have a large number of defect structures, which can provide a large amount of polarization loss and enhance the absorption capacity of electromagnetic waves. Therefore, it is an ideal choice as the carbon matrix material in carbide / carbon composite absorbing materials.
[0005] Patent CN 116507102 A discloses the preparation of composite absorbing material precursor: mixing a substance containing dielectric absorbing material elements with graphite powder; preparing a plasma anode: pouring the composite absorbing material precursor into the holes of a porous graphite rod and drying; preparing a carbon nanohorn composite absorbing material: using a pure graphite rod as a cathode, and placing the prepared plasma anode into an arc furnace, after the arc furnace is evacuated, the arc furnace is filled with a preset gas and the arc is started. After the reaction is completed, the sediment on the inner wall of the reaction chamber is collected and sieved to obtain a carbon nanohorn composite absorbing material. However, it is difficult to obtain an ideal product using the arc discharge conditions involved in the patent. Therefore, how to optimize the arc discharge process to synthesize lightweight carbides and molybdenum carbide / carbon nanohorn composite materials is a difficulty that needs to be overcome at present. Summary of the invention
[0006] In order to overcome the problems of complex preparation process and heavy weight of molybdenum carbide / carbon nanohorn composite materials in the prior art, the purpose of the present invention is to provide a preparation method and application of a corrosion-resistant broadband carbon-based absorbing material. The process of the method is simple, and the prepared corrosion-resistant broadband carbon-based absorbing material has the advantages of low density and light weight.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a corrosion-resistant broadband carbon-based absorbing material comprises the following steps:
[0009] After the interface distance between the cathode and the anode with titanium wire and molybdenum wire is set to a set distance, discharge arc is started in a mixed atmosphere of N2 and Ar to obtain a corrosion-resistant broadband carbon-based absorbing material.
[0010] A further improvement of the present invention is that the anode with the titanium wire and the molybdenum wire is made by the following process: a hole is opened in the anode, and the titanium wire and the molybdenum wire are placed in the hole.
[0011] A further improvement of the present invention is that the set distance is determined according to the arc starting distance between the cathode and the anode.
[0012] A further improvement of the present invention is that when the discharge arc is started, the discharge process lasts for 6-7 seconds.
[0013] A further improvement of the present invention is that the diameter and length of the titanium wire and the molybdenum wire are the same.
[0014] A further improvement of the present invention is that the ratio of the number of titanium wires to the number of molybdenum wires is 1:1, 2:1 or 1:2.
[0015] A further improvement of the present invention is that the diameter of the anode is 6 mm and the length is 8 cm; the diameter of the molybdenum wire is 0.5 mm and the length is 5 cm.
[0016] A further improvement of the present invention is that the pressure of N2 is 0.02MPa and the pressure of Ar is 0.13MPa.
[0017] A corrosion-resistant broadband carbon-based absorbing material.
[0018] The invention discloses an application of a corrosion-resistant broadband carbon-based absorbing material in the preparation of absorbing materials.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention utilizes a positive high-voltage (>1atm) DC arc discharge method to successfully prepare high-purity and low-cost carbon nanohorns in nitrogen and argon atmospheres, and by using an anode with titanium wire and molybdenum wire, a nitrogen-doped carbon nanohorn composite material coated with MoC and TiC nanoparticles, i.e., a corrosion-resistant broadband carbon-based wave-absorbing material, can be synthesized in one step. Among them, the high-pressure atmosphere can reach the carbonization temperature of the metal molybdenum wire and the titanium wire, so that they are carbonized to form MoC and TiC, and both MoC and TiC have excellent stability. In a harsh marine environment with high humidity, while meeting the wave-absorbing requirements, they can protect ships to a certain extent and delay their corrosion, and the introduction of TiC reduces the density of the composite material, reduces its quality, and expands its practical application range. In the present invention, due to the high-pressure atmosphere, the furnace can reach a high temperature of 4000-5000K, and the metal wire inserted in the carbon rod can reach the carbonization temperature to be carbonized, and the product can be obtained by one-step synthesis, and the obtained product has high purity, high yield, simple process, and is suitable for large-scale production.
[0021] The carbon nanohorns, MoC and TiC in the corrosion-resistant broadband carbon-based absorbing material prepared by the present invention all have excellent stability. In a harsh marine environment with high humidity, they can protect ships to a certain extent and delay their corrosion while meeting the absorption requirements. The introduction of TiC reduces the density of the composite material, reduces its quality, and expands its practical application range. The corrosion-resistant broadband carbon-based absorbing material prepared by the present invention has both dielectric properties and magnetic properties, and the nitrogen atmosphere successfully dopes nitrogen atoms, provides more defects for the material, strengthens the polarization loss of the material, and thus has a strong electromagnetic loss capacity and a wide absorption bandwidth, showing excellent absorbing performance. The corrosion-resistant broadband carbon-based absorbing material prepared by the present invention is a coating structure, and the carbon nanohorn matrix of the outer layer has good hydrophobicity, which can serve as a barrier to protect the internal nanoparticles and prevent them from being corroded. In addition, MoC and TiC, as transition metal compounds, both have excellent stability, which also provides certain support for the corrosion resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 It is a mechanism diagram of the preparation method of the present invention;
[0024] Figure 2 TEM spectrum of Example 1; wherein (a) is a low magnification, and (b) is a high magnification;
[0025] Figure 3 1 is a reflection loss diagram of three samples in Example 1, Example 2 and Example 3; wherein (a) is a reflection loss diagram of Example 1, (b) is a reflection loss diagram of Example 2, and (c) is a reflection loss diagram of Example 3;
[0026] Figure 4 The OCP curves and Tafel curves of the samples in Example 1, Example 2 and Example 3, as well as the pure epoxy resin coating and the blank working electrode; wherein (a) is the OCP curve, and (b) is the Tafel curve. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0028] The principle of DC arc discharge method is: when a DC current of a unit mass passes through the gap between two conductors (electrodes), if the gas or metal vapor in the gap is ionized, a conductive channel, i.e., an arc, can be formed. In this process, gas molecules or atoms produce free electrons and positive ions due to ionization, making the originally non-conductive gas gap conductive. After the arc is formed, a large amount of heat energy will be generated due to the passage of current and the continuation of the ionization process. This heat energy causes the temperature of the arc to rise sharply, which can reach thousands to tens of thousands of degrees. At high temperatures, the arc can melt, evaporate, and even decompose the materials it contacts.
[0029] The reason for filling the arc furnace with N2 and Ar is that N2 (nitrogen) and Ar (argon) are both inert gases. They are not easy to react chemically with other substances, so they can effectively protect the materials in the arc furnace from oxidation. During the arc discharge process, high temperature will cause oxidation on the surface of the material, resulting in a decrease in material performance. Filling N2 and Ar can significantly reduce the occurrence of oxidation reactions, thereby maintaining the original performance of the material. The filling of N2 and Ar can stabilize the arc discharge process and reduce the flickering and instability of the arc. This helps to ensure the continuity and stability of the discharge process, thereby improving the efficiency and quality of the prepared materials. The temperature of the arc can be further adjusted by adjusting the charging ratio of N2 and Ar. This helps to optimize the thermal effect in the preparation process, so that the material melts, evaporates and reacts at an appropriate temperature. And during the arc discharge process, the filling of N2 and Ar can promote the synthesis reaction between materials. For example, they can react with carbon materials to form carbon-based absorbing materials with special structures and properties.
[0030] See also Figure 1 The method for preparing a corrosion-resistant broadband carbon-based absorbing material of the present invention comprises the following steps:
[0031] First, drill a hole with a diameter of 3mm and a length of 5cm on a graphite anode with a diameter of 6mm and a length of 8cm to insert titanium wire and molybdenum wire. Insert the titanium wire and molybdenum wire into the anode, and put the graphite anode into the anode hole, and then wipe the cathode rod clean and put it in the cathode hole. Adjust the interface distance between the cathode and anode carbon rods to about 1-2mm, close the arc furnace door, and seal it well. Then evacuate the arc furnace, and after completion, fill the arc furnace with N2 and Ar. After the filling is completed, discharge and arcing are carried out. Each arcing process is guaranteed to last for 6-7 seconds. At the same time, adjust the anode propeller during arcing to ensure that the arcing distance between the carbon rods is always reached. After the discharge is completed, the furnace samples can be collected after natural cooling for about 8 hours to obtain corrosion-resistant broadband carbon-based absorbing materials.
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] (1) First, drill a hole with a diameter of 3 mm and a length of 5 cm on a graphite anode with a diameter of 6 mm and a length of 8 cm to insert the titanium wire and molybdenum wire. Insert a molybdenum wire (one piece) with a diameter of 0.5 mm and a length of 5 cm and a titanium wire in a ratio of 1:1 into the anode, and then wipe the cathode rod clean and place it in the cathode hole. To achieve the arc starting distance, adjust the interface distance between the cathode and anode carbon rods to about 2 mm, close the furnace door, and make a good seal.
[0035] (2) Then close the air valve, open the gas cylinder valve and the vacuum pump valve, and evacuate the arc furnace. After evacuation, fill the arc furnace with 0.02MPa N2 and 0.13MPa Ar.
[0036] (3) After the gas filling is completed, the gas cylinder valve is closed, and the electric welder is turned on to start the discharge arc. Each arcing process is guaranteed to last for 6-7 seconds. During the arcing process, the anode thruster is adjusted to ensure that the arcing distance between the carbon rods is always reached. After the discharge is completed and the temperature is lowered, the samples on the furnace wall can be collected, that is, the corrosion-resistant broadband carbon-based absorbing material.
[0037] Example 2
[0038] The same as Example 1, except that the ratio of the number of inserted metal molybdenum wire (one wire) to titanium wire is 1:2.
[0039] Example 3
[0040] The same as Example 1, except that the ratio of the number of inserted metal molybdenum wires (two wires) to the number of inserted titanium wires is 2:1.
[0041] See also Figure 1 After filling with nitrogen and argon and starting to discharge, the temperature in the furnace gradually increases, up to 4000-5000K. The anode graphite can evaporate to form carbon "steam", nucleating and growing into carbon nanohorns. At the same time, the metal wire inserted in the anode graphite rod can be carbonized to form metal carbide.
[0042] See also Figure 2 In (a) and (b), it can be seen that TiC and MoC are successfully generated and encapsulated inside the carbon nanohorns. The hydrophobic outer layer of the carbon nanohorns can act as a barrier to protect the internal materials.
[0043] See also Figure 3In (a), (b) and (c), it can be seen that the strongest reflection loss of the sample in Example 1 can reach -50.89GHz at a thickness of 1.8mm, and the maximum effective absorption bandwidth can reach 5.27GHz; the strongest reflection loss of the sample in Example 2 can reach -45.58GHz, and the maximum effective absorption bandwidth can reach 5.78GHz at a thickness of 1.7mm; the strongest reflection loss of the sample in Example 3 can reach -35.24GHz, and the maximum effective absorption bandwidth can reach 5.87GHz at a thickness of 1.8mm. It can be seen that the carbon-based absorbing material prepared by this method has the characteristics of strong loss, wide bandwidth and low thickness.
[0044] Wave absorption performance test:
[0045] The corrosion-resistant broadband carbon-based absorbing materials prepared in Examples 1, 2 and 3 were mixed with 30wt% paraffin and pressed into concentric rings with a thickness of 2.0mm, an inner diameter of 3.04mm and an outer diameter of 7.0mm. The electromagnetic parameters of the samples in the range of 2-18GHz were measured using a vector network analyzer. The reflection loss of the samples was calculated using the transmission line formula. All three samples showed strong loss capacity and wide absorption bandwidth, with the strongest reflection loss reaching -5.87GHz and the maximum effective absorption bandwidth reaching 5.87GHz.
[0046] Corrosion resistance test:
[0047] (1) Preparation of working electrode: The working electrode is made of 1*1 cm carbon steel (Q235) after sandpaper grinding and polishing. First, the copper wire is glued to its back with conductive glue, and after it is firmly bonded, it is embedded in the mold. Then, epoxy resin and polyamide are mixed in a weight ratio of 3:1 and poured into the mold. After the colloid is completely solidified at room temperature, the working electrode is removed from the mold for the next electrochemical test.
[0048] (2) Preparation of epoxy resin composite coating: First, 20 mg of the corrosion-resistant broadband carbon-based absorbing materials prepared in Example 1, Example 2 and Example 3 were dissolved in acetone solution respectively, mixed with 2 g of epoxy resin, and then continuously ultrasonicated for 30 minutes. Subsequently, 2 g of polyamide was added and heated and stirred for 30 minutes to eliminate acetone. In this way, a composite anti-corrosion coating with uniform and moderate viscosity was obtained. Finally, the coating was applied to the working electrode and cured at room temperature for 5 days to obtain an epoxy-based composite anti-corrosion coating. Pure epoxy resin coating without adding corrosion-resistant broadband carbon-based absorbing material and a blank uncoated working electrode were prepared in the same way as controls.
[0049] See also Figure 4 In (a) and (b), it can be seen that the open circuit potential of the coating with the addition of corrosion-resistant broadband carbon-based absorbing material has been improved, and the coating provides a certain degree of corrosion resistance.
[0050] (3) Anti-corrosion performance test: A 3.5wt% NaCl solution was used as the electrolyte to simulate the marine environment, and the electrochemical data of the epoxy-based composite anti-corrosion coating was measured using an electrochemical workstation with a traditional three-electrode test system. In order to achieve electrochemical stability, a 1-hour open circuit potential (OCP) test was first carried out. Subsequently, the relationship between the Tafel polarization dynamic curve and OCP was measured at a scanning rate of 1mV / s in the voltage range of -0.25 to 0.25V. It was calculated that the corrosion rate of the sample can be reduced by 3-4 orders of magnitude compared to uncoated protection, and can be reduced by 2-3 orders of magnitude compared to pure epoxy resin coating protection, showing excellent corrosion resistance. See Table 1 for specific corrosion rates.
[0051] Table 1 Corrosion rate
[0052]
[0053]
[0054] It can be seen from Table 1 that the corrosion-resistant broadband carbon-based absorbing material prepared in the embodiment of the present invention has a lower corrosion rate than the pure epoxy resin coating and the uncoated working electrode, which is 1.25×10 -5 mm / a, has good corrosion resistance.
[0055] The present invention utilizes a positive high-voltage (>1atm) DC arc discharge method to successfully prepare a high-purity and low-cost corrosion-resistant broadband carbon-based absorbing material in a nitrogen and argon atmosphere, and by inserting metal molybdenum wire and titanium wire into an anode carbon rod, a nitrogen-doped carbon nano-horn composite material coated with MoC and TiC nanoparticles, i.e., a corrosion-resistant broadband carbon-based absorbing material, can be synthesized in one step. The high-pressure atmosphere can make the furnace reach the carbonization temperature of the metal molybdenum wire and titanium wire, so that they are carbonized to form MoC and TiC, which provides a simple preparation method for corrosion-resistant broadband carbon-based absorbing materials.
[0056] The corrosion-resistant broadband carbon-based absorbing material prepared by the present invention is a carbon nanohorn material. Both MoC and TiC have excellent stability. In a harsh marine environment with high humidity, they can protect ships to a certain extent and delay their corrosion while meeting the absorbing requirements. The introduction of TiC reduces the density of the composite material, reduces its quality, and expands its practical application range. The main advantages are:
[0057] (1) The preparation process of the present invention is simple. Due to the high-pressure atmosphere, the temperature in the furnace can reach 4000-5000K, and the metal wire inserted in the carbon rod can reach the carbonization temperature to be carbonized. The product can be obtained by one-step synthesis, and the obtained product has high purity and high yield, which is suitable for large-scale production.
[0058] (2) The corrosion-resistant broadband carbon-based absorbing material of the present invention has both dielectric properties and magnetic properties, and the nitrogen atmosphere successfully dopes nitrogen atoms, providing more defects for the material and enhancing the polarization loss of the material. Therefore, it has a stronger electromagnetic loss capacity and a wider absorption bandwidth, showing excellent absorbing performance.
[0059] (3) The corrosion-resistant broadband carbon-based absorbing material of the present invention is a coating structure. The outer carbon nanohorn matrix has good hydrophobicity and can act as a barrier to protect the inner nanoparticles and prevent them from being corroded. In addition, MoC and TiC, as transition metal compounds, both have excellent stability, which also provides certain support for the corrosion resistance of the composite material.
[0060] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0061] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a corrosion-resistant broadband carbon-based absorbing material, characterized in that: The following steps are involved: After the interface distance between the cathode and the anode with titanium wire and molybdenum wire is set to a set distance, discharge arc is started in a mixed atmosphere of N2 and Ar to obtain a corrosion-resistant broadband carbon-based absorbing material.
2. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1, characterized in that: The anode with the titanium wire and the molybdenum wire is manufactured by the following process: a hole is opened in the anode, and the titanium wire and the molybdenum wire are placed in the hole.
3. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1, characterized in that: The set distance is determined according to the arc starting distance between the cathode and the anode.
4. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1, characterized in that: When the discharge arc starts, the discharge process lasts for 6-7 seconds.
5. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1, characterized in that: The titanium wire and molybdenum wire have the same diameter and length.
6. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1 or 5, characterized in that: The quantity ratio of the titanium wire to the molybdenum wire is 1:1, 2:1 or 1:
2.
7. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1 or 5, characterized in that: The diameter of the anode is 6 mm and the length is 8 cm; the diameter of the molybdenum wire is 0.5 mm and the length is 5 cm.
8. The method for preparing the corrosion-resistant broadband carbon-based absorbing material according to claim 1, characterized in that: The pressure of N2 is 0.02 MPa, and the pressure of Ar is 0.13 MPa.
9. A corrosion-resistant broadband carbon-based absorbing material prepared according to the method according to any one of claims 1 to 8.
10. Use of the corrosion-resistant broadband carbon-based absorbing material prepared according to the method according to any one of claims 1 to 8 in the preparation of absorbing materials.